The Religious Oral Tradition of ‘Maca Syekh’ and the Concept of Preserving Oral Literature in Schools - Sukirmo Sukirno; Bayu Suta Wardianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
Maca Syekh or also called Macaseh is a popular and preserved religious oral tradition in Banten. The reading of the Maca Syekh was done to exemplify the struggle of Sheikh Abdur Qadir Al-Jaelani who was a great worldwide cleric. This long-standing religious rite has seen its implementation decline as it competes with other cultures that are increasingly unstoppable. This study intends to express the importance of the implementation of the Maca Syekh which is described in the descriptions. The method carried out in this study is descriptive qualitative by presenting its analysis using reflective conceptual techniques. The results obtained after that knowing the importance of Maca Syekh, became the basis for efforts to maintain religious oral traditions by mixing them with the concept of literary learning and collaborating with History and Islamic studies at the level of education in high school.